#### Answer

4

#### Work Step by Step

$\frac{6 + 3 \times (2)}{(3)}$ =
$\frac{6 + 6}{3}$ =
$\frac{12}{3}$ =
4

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

4

$\frac{6 + 3 \times (2)}{(3)}$ =
$\frac{6 + 6}{3}$ =
$\frac{12}{3}$ =
4

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.